Toxic Effect of Amitriptyline An antidepressant Drug on Drosophila melanogaster - Nazari, Mansoor (Journal of Postgraduate Medical Institute, 2011)
the objective of this study wa to evaluate the genotoxic effect of amitriptyline on a fruit fly D melanogaster and to make suggestions if any for its use. The pure strain of drosophila melanogaster (oregon K) was used for experiments. The pure culture was maintained under the laboratory condition at a temperature 24 + 2 C. Standard food medium (wheat cream agar medium) was used for maintenance of Drosophila flies in the laboratory. Eggs of the same age collected by procedure of Delocour. LC50 amitriptyline for the larval feeding method was estimated (0.21%) then, sub lethal concentrations of 0.05, 0.1, 0.2 and 0.3% of amitriptyline were selected. Amitriptyline has effect on viability eclosion and developmental time but not on sex ratio of drosophila melanogaster.